Impact of Manufacturing Procedures on CAR T Cell Functionality - Watanabe, Norihiro; Mo, Feiyan; McKenna, Mary Kathryn (Frontiers in Immunology, 2022)
The field of chimeric antigen receptor (CAR) modified T cell therapy has rapidly expanded in the past few decades. As of today, there are six CAR T cell products that have been approved by the FDA: KYMRIAH (tisagenlecleucel, CD19 CAR T cells), YESCARTA (axicabtagene ciloleucel, CD19 CAR T cells), TECARTUS (brexucabtagene autoleucel, CD19 CAR T cells), BREYANZI (lisocabtagene maraleucel, CD19 CAR T cells), ABECMA (idecabtagene vicleucel, BCMA CAR T cells) and CARVYKTI (ciltacabtagene autoleucel, BCMA CAR T cells). With this clinical success, CAR T cell therapy has become one of the most promising treatment options to combat cancers. Current research efforts focus on further potentiating its efficacy in non-responding patients and solid tumor settings. To achieve this, recent evidence suggested that, apart from developing next-generation CAR T cells with additional genetic modifications, ex vivo culture conditions could significantly impact CAR T cell functionality – an often overlooked aspect during clinical translation. In this review, we focus on the ex vivo manufacturing process for CAR T cells and discuss how it impacts CAR T cell function.